Shareloc: An Analysis of Isekai Elements Across Different Genre and Cinematic Cultures - Cahyaningtyas, Ardelia Elvina; Safitri, Ardita Wahyu; Saputri, Andriani Ika; Yuliana, Siti Komsiyah (Politeknik Assalaam Surakarta, 2025)
The Isekai genre stories where characters are transported from their familiar world to a fantastical or parallel reality has gained significant popularity across various media. However, its presence in films from different cultural contexts has received less scholarly attention. The objective of this research is to explore the Isekai elements found in ‘Along with the Gods: The Two Worlds’, ‘Saranjana Kota Ghaib’, ‘Spirited Away’, and ‘Jumanji: Welcome to the Jungle’. This study aims to analyze how the movie genres aligned with the Isekai elements through the characters journey. This research employed a descriptive qualitative method to analyze both textual and visual elements derived from narrative components and scenes depicting character teleportation or Isekai transitions. The analysis followed (Spradley, 2016) method, which consists of four phases: domain, taxonomy, componential, and cultural theme. In the domain analysis phase, (Mendlesohn, 2014) theory of Isekai was applied. The analysis reveals that Isekai appears in various genres, including adventure, action, and horror, in the four selected films, featuring elements such as portal-quest, liminal, and intrusion. This research helps readers apply Isekai elements to diverse creative works, such as video games, novels, films, and poetry